A new species of Merothrips from the Dampa Tiger Reserve, Mizoram, India (Thysanoptera, Terebrantia) - Johnson, Th.; Mound, L.a.; Varatharajan, R. (Zootaxa, 2021)
Merothrips mizoramensis sp.n. is described from northeastern India based on a single macropterous female. The fore wings of this specimen have a single longitudinal vein, the pronotal notopleural sutures are very long with the posteroangular setae displaced laterally, tergite IX lacks trichobothria, and many tergites and sternites bear an unusual number of sculptured lines.